A Summary of Chinese Guidelines on Diagnosis and Management of Hyperglycemia in Pregnancy (2022) - Chen Wang; Juan Juan; Huixia Yang (Maternal-Fetal Medicine)
Abstract. Hyperglycemia is one of the most common complications women encounter during pregnancy, and is associated with a higher incidence of short- and long-term health risks for both the mother and offspring. In 2022, the Maternal-Fetal Medicine Committee of the Chinese Society of Obstetrics and Gynecology, Chinese Medicine Association, worked with the Chinese Society of Perinatal Medicine and the Professional Committee of Gestational Diabetes Mellitus of the Chinese Maternal and Child Health Association to update the Guidelines for the diagnosis and management of hyperglycemia in pregnancy in China. The aim was to further standardize the management of hyperglycemia in pregnancy from the aspects of screening, diagnosis, monitoring, treatment, and prevention of gestational diabetes mellitus, and consequently to further improve the health of mother and child.